Richard Hooker and the Christian Virtues - Graves, Daniel F.,; Kindred-Barnes, Scott N., (Early Modern History and Modern History E-Books Online, Collection 2024., 2024)
The contributors to the volume explore the relationship of the virtues to Richard Hooker's ontology, to questions of justification by faith, how righteousness is appropriated by the Christian, how the virtues relate to his polemical context, what he takes from both Scripture and his theological forbearers, and how he demonstrates the virtues in his own literary persona. Contributors include: Benjamin Crosby, Paul Dominiak, Daniel Eppley, AndrÃ© A. Gazal, Daniel F. Graves, Dan Kemp, Scott N. Kindred-Barnes, W.J. Torrance Kirby, W. Bradford Littlejohn, Arthur Stephen McGrade, W. David Neelands, and John K. Stafford.